Gambaran umum berbagai faktor keterlambatan pemberian nutrisi enteral pada pasien anak di Ruang Rawat Intensif Anak, RSUP Sanglah, Denpasar, Bali - Ni Luh Sri Apsari; I Gusti Lanang Sidiartha; I Nyoman Budi Hartawan; Dyah Kanya Wati; Ida Bagus Gede Suparyatha (DiscoverSys Inc., 2019)
Background: Enteral nutrition is the primary choice in pediatric patients who do not experience gastrointestinal disorders. Many factors inhibit the achievement of enteral nutrition in pediatric patients treated in intensive care. This study aims to determine the overview of various factors that may result in delays enteral nutrition administration in critically ill pediatric patientsMethods: An observational cross-sectional analytic study was carried out on secondary data of medical records among children who were treated in pediatric intensive care unit at Sanglah Hospital throughout 2016. Delay in enteral nutrition was assessed if there was enteral nutrition administration more than 2x24 hours since first admission. Factors assessed include gender, age, PELOD, diagnosis, invasive breathing aids, impaired motility, gastrointestinal bleeding, and hemodynamic instability. Data were analyzed using the SPSS version 20 software program whereas P value <0.05 was considered statistically significant.Results: From the 115 samples, there were 69 (60%) males and 46 (40%) females. About 50 samples (43,5%) experienced delayed enteral nutrition. Significant variables related to the delay in enteral nutrition after multivariate analysis were gastrointestinal motility disorders (p = 0,004, OR 9,082, 95% IK 2,827 – 29,171), and gastrointestinal bleeding (p = 0,0001; OR 14,317; IK 95 % 4,087 – 50,155).Conclusion Intestinal motility disorders and gastrointestinal bleeding are known as a contributing factor in the delay of enteral nutrition administration in PICU Sanglah Hospital, Denpasar, Bali.